2017
DOI: 10.1016/j.bjpt.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-rater reliability of neutral head position and target head position tests in patients with and without neck pain

Abstract: Highlights•Neutral head and target head position tests evaluate cervical proprioception.•Clinics commonly use those position tests, and it is important to test their reliability.•Intra- and inter-rater reliability was moderate to high for these tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 46 publications
3
46
1
1
Order By: Relevance
“…Encouragingly, similar inter-rater reliability values for error frequency (ICC = 0.93) were shown in the Australian study of asymptomatic controls who overall demonstrated less mean errors than the neck pain subjects in the current study [ 21 ]. Furthermore, intra-rater reliability shown in our study is comparably high to values reported for rating similar test procedures like joint position error (JPE) measurements [ 36 , 37 ]. In a study requiring head repositioning after neck rotation or flexion/extension returning to a neutral and target head position, similar ICCs and SEMS to our results were reported (intra: ICC between 0.70–0.83, SEM 1.45–2.45; inter: 0.62–0.84, SEM 1.50–2.23) [ 36 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Encouragingly, similar inter-rater reliability values for error frequency (ICC = 0.93) were shown in the Australian study of asymptomatic controls who overall demonstrated less mean errors than the neck pain subjects in the current study [ 21 ]. Furthermore, intra-rater reliability shown in our study is comparably high to values reported for rating similar test procedures like joint position error (JPE) measurements [ 36 , 37 ]. In a study requiring head repositioning after neck rotation or flexion/extension returning to a neutral and target head position, similar ICCs and SEMS to our results were reported (intra: ICC between 0.70–0.83, SEM 1.45–2.45; inter: 0.62–0.84, SEM 1.50–2.23) [ 36 ].…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, intra-rater reliability shown in our study is comparably high to values reported for rating similar test procedures like joint position error (JPE) measurements [ 36 , 37 ]. In a study requiring head repositioning after neck rotation or flexion/extension returning to a neutral and target head position, similar ICCs and SEMS to our results were reported (intra: ICC between 0.70–0.83, SEM 1.45–2.45; inter: 0.62–0.84, SEM 1.50–2.23) [ 36 ]. Juul et al [ 37 ] reported lower ICCs but better SEMs in examining the reliability of rating JPE returning to a neutral head position from rotation, extension and flexion (intra: ICC 0.48–0.82, SEM 0.19–0.26; inter: ICC 0.50–0.75, SEM 0.20–0.50).…”
Section: Discussionsupporting
confidence: 75%
“…For measuring cervical JPE, this study adopted the active head repositioning to the target method, which several authors previously used in clinical settings and was found to be a reliable method [12,39]. The number of testing trials or movement repetitions in each direction was limited to three to minimize the effect of fatigue of cervical muscles on JPE.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated cervical proprioception as cervical joint position errors in degrees, adapting the joint position errors testing protocol from Alahmari al. 's study [12]. Moreover, we estimated joint position errors following the subject's ability to actively reposition their head to a target position that the examiner previously demonstrated.…”
Section: Cervical Proprioceptionmentioning
confidence: 99%
“…Neutral head position method was used to evaluate proprioception in flexion, extension, rotation and lateral flexion in right and left movement directions at sitting position (figure 1). 5 Three measures were performed, and the average of the three trials was used for analysis. The distance between zero spot and joint position which patient had been reconstructed was measured by centimetre.…”
mentioning
confidence: 99%